Polímeros de coordenação: estratégias, design de ligantes oxamato, síntese e caracterização - Kalinke, Lucas Hoffmann Greghi (2019)
This present work presents the synthesis and characterization of some coordination compounds containing oxamato ligands with different topologies. The precursor 1 and the chain (1D) Mn-Cu (7) with the H2Et2npbo ligand [npbo= N,N’-(naphtalene-1,8-diyl)-bis(oxamato)], the plane (2D) Ca3-Cu9 (8) with the H2Et2dabtzo ligand [dabtzo= N,N'-(4,4'-bithiazole-2,2'-diyl)-bis(oxamato)] and the 3D polymers M6-Co4 [M= Ca (9), Dy (10), Er (11) Ho(12) e Tb(13)] all of them with the H3Et3tpatox ligand [tpatox= N,N',N''-(nitrilotris(phenilene-4,1-diyl))-tris(oxamato)]. In addition were prepared precursor complexes of Cu(II) (2 and 3) and Co(II) (4) also with the H2Et2dabtzo ligand and the Ni(II) complex (6) with the H4Et4topp ligand [topp= N,N’,N’’,N’’’-tetrakis(4-aminophenyl)porphyrin-tetrakis(oxamato)]. The crystal structures of 2, 4, 7-12 were determined by single-crystal X ray diffraction. The magnetic properties of 8 have shown that Cu9 unit behaves as a trimer of trimers with different magnetic exchange paths between the Cu(II) ions. The magnetic properties for the polymers 10-13 reveal the behavior as magnetically isolated lanthanide ion with ground 6H15/2 (DyIII), 4I15/2 (ErIII), 5I8 (HoIII) e 7F6(TbIII); with Mj= ±½ (10 e 11) and Mj= 0 (12 e 13). Furthermore, the polymeric compounds 10 e 11 have shown slow magnetic relaxation with Ea and  been determined by the Arrhenius law.